2018
DOI: 10.1016/j.scitotenv.2018.06.089
|View full text |Cite
|
Sign up to set email alerts
|

Acute peat smoke inhalation sensitizes rats to the postprandial cardiometabolic effects of a high fat oral load

Abstract: Wildland fire emissions cause adverse cardiopulmonary outcomes, yet controlled exposure studies to characterize health impacts of specific biomass sources have been complicated by the often latent effects of air pollution. The aim of this study was to determine if postprandial responses after a high fat challenge, long used clinically to predict cardiovascular risk, would unmask latent cardiometabolic responses in rats exposed to peat smoke, a key wildland fire air pollution source. Male Wistar Kyoto rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Though minimal immune cell changes were observed in the bronchoalveolar lavage fluid (BALF), high doses of peat smoke PM extract (350 μg per animal) led to altered regulation of ventricular ejection and filling volumes, affecting blood flow in the pulmonary circulation [ 148 ]. In a study investigating the cardiometabolic responses to a high fat diet, rats exposed to peat fire smoke for 1 h showed increases in serum high-density lipoprotein (HDL) and total cholesterol, as well as increased isovolumic heart relaxation time after high fat food challenge, compared to values seen in control rats exposed to filtered air [ 93 ].…”
Section: Cardiovascular Effects Of Wildfire Smokementioning
confidence: 99%
“…Though minimal immune cell changes were observed in the bronchoalveolar lavage fluid (BALF), high doses of peat smoke PM extract (350 μg per animal) led to altered regulation of ventricular ejection and filling volumes, affecting blood flow in the pulmonary circulation [ 148 ]. In a study investigating the cardiometabolic responses to a high fat diet, rats exposed to peat fire smoke for 1 h showed increases in serum high-density lipoprotein (HDL) and total cholesterol, as well as increased isovolumic heart relaxation time after high fat food challenge, compared to values seen in control rats exposed to filtered air [ 93 ].…”
Section: Cardiovascular Effects Of Wildfire Smokementioning
confidence: 99%
“…In the oral toxicity study, we found that the acute oral LD 50 of rEP was greater than 5 g/kg body weight in female rats. This result shows that even a very high concentration did not cause notable toxicity in test animals [33]. In addition, no mortality or significant variations in body weight were observed.…”
Section: Discussionmentioning
confidence: 58%
“…Tests like oral toxicity, inhalation toxicity, eye irritation, and skin sensitization are commonly conducted to assess the safety of test molecules [31]. Acute oral toxicity is generally evaluated by oral gavage of rats [32][33][34]. Similarly, acute inhalation toxicity studies are performed by exposing rat models to liquid aerosols for a given period of time [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although air pollution from wildfire smoke is known to cause respiratory irritation and damage, its effect on the central nervous system is not well described. The problem of the adverse mental health effects caused by particulate matter is of particular relevance [13][14][15]. Current evidence links wood smoke exposure to cognitive dysfunction, including dementia and Alzheimer's disease [16].…”
Section: Introductionmentioning
confidence: 99%